“O corpo de Deus”: administrando controvérsias entre o corpo algorítmico do movimento pós-humanista e o simbolismo religioso da corporeidade humana. - SILVA, Emerson da (2023)
This thesis proposes a critical evaluation of the post-humanist philosophy's understanding of human corporeity, refuting its abstract comprehension of reality, which goes from modern theories of a dualistic nature that shaped the critical thinking of that time to the critical approach of the body as such. A series of socio-cultural and techno-scientific events gave rise to considerable changes in what is conventionally called "Humanism" in the West. Among those changes is the idea that human beings cannot be seen under the limits of its corporality as it originally used to be, and this becomes the next "humanist" goal to be considered by scholars committed to it. Considering this, this thesis uses the religious symbolism of the body found in the Christian language in terms of an "epistemology of controversies" - a theoretical and methodological contribution linked to the new theories of complexity that emerged in scientific research from the first half of the 20th century. Hence, this study presents a new configuration of the impasse between humanists and post-humanists about the meaning of human corporeity. The Husserlian notion of the "lived body" is defended in this work as fundamental for Western humanism and reinterpreted through religious semantics, providing a productive dialogue between science and religion and a critical direction for the dispute in question. The thesis has a qualitative, exploratory, and bibliographic character, constituting an unprecedented contribution to the interdisciplinary field of Sciences of Religion, which deals with a comprehensive dialogue of areas such as complex thinking, religious discourse, and cyberculture.